Memahami Keragaman Budaya dan Teori Budaya Organisasi - Ansori Ansori; Ratmelia Ratmelia; Annisah Annisah; Samudra Purnama (Institut Nalanda, 2024)
Culture arises from human wisdom and/or power, creativity, work, intention, thoughts, and customs, whether consciously or unconsciously, and can be recognized as civilized behavior. It defines the way of life within an organization. Organizational culture encompasses the emotional and psychological climate or atmosphere. It also encompasses all symbols (actions, routines, conversations, etc.) and their associated meanings between employees and management. Pacanowsky and O'Donnell introduced organizational culture theory, which significantly influences theory and research in organizational communication. They are among several researchers who explore organizational life by examining both employees and their behaviors.